Governance, capital flight and industrialisation in Africa - Simplice Asongu; Nicholas M. Odhiambo (Journal of Economic Structures, 2019)
The study examines the role of governance in modulating the effect of capital flight on industrialisation in Africa. The empirical evidence is based on Generalised Method of Moments and governance is bundled by principal component analysis, namely (i) political governance from political stability and "voice and accountability"; (ii) economic governance from government effectiveness and regulation quality; and (iii) institutional governance from corruption-control and the rule of law. First, governance increases industrialisation whereas capital flight has the opposite effect; and second, governance does not significantly mitigate the negative effect of capital flight on industrialisation. Policy implications are discussed.
Keywords: C50; F34; G38; O14; O55; 330; Econometric modelling; Capital fight; Governance; Industrialisation; Africa